2021
DOI: 10.3390/ijms22158055
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin Spectroscopy: From Biomedical Research to New Generation Pathology Diagnosis

Abstract: Brillouin spectroscopy has recently gained considerable interest within the biomedical field as an innovative tool to study mechanical properties in biology. The Brillouin effect is based on the inelastic scattering of photons caused by their interaction with thermodynamically driven acoustic modes or phonons and it is highly dependent on the material’s elasticity. Therefore, Brillouin is a contactless, label-free optic approach to elastic and viscoelastic analysis that has enabled unprecedented analysis of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…The resultant Brillouin frequency shift can be used to calculate the elastic (longitudinal) modulus of the sample if its density and refractive index are known. BM is currently being used and developed for diverse applications in biomedical research such as ophthalmological pathologies and basic research such as mouse embryogenesis, zebrafish development and regeneration, and cell biology [ 34 , 35 , 36 ]. Recent work has indicated that for most common biological samples the Brillouin shift can be used as a proxy for the sample’s mechanical properties [ 31 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant Brillouin frequency shift can be used to calculate the elastic (longitudinal) modulus of the sample if its density and refractive index are known. BM is currently being used and developed for diverse applications in biomedical research such as ophthalmological pathologies and basic research such as mouse embryogenesis, zebrafish development and regeneration, and cell biology [ 34 , 35 , 36 ]. Recent work has indicated that for most common biological samples the Brillouin shift can be used as a proxy for the sample’s mechanical properties [ 31 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant Brillouin frequency shift can be used to calculate the elastic (longitudinal) modulus of the sample, if its density and refractive index are known. BM is currently being used and developed for diverse applications in biomedical research such as ophthalmological pathologies and basic research such as mouse embryogenesis, zebrafish development and regeneration, and cell biology (34)(35)(36). Recent work has indicated that for most common biological samples the Brillouin shift can be used as a proxy for the sample's mechanical properties (31) (42).…”
Section: Introductionmentioning
confidence: 99%
“…Brillouin light scattering deals with the interaction of the incident light with acoustic waves, spontaneously propagating in the matter thermally activated [10,13]. In the Brillouin spectra, the peaks' intensity is directly dependent on the concentration of the elastic species supporting the acoustic mode, whereas the square of its Brillouin frequency shift, ν B , is related to the elastic species hardness, expressed by the longitudinal elastic modulus M:…”
Section: Brillouin Data Analysismentioning
confidence: 99%
“…Brillouin and Raman micro-spectroscopy (BRmS) is an optical correlative method for material characterization at the microscale based on light scattering [10,11]. Specifically, Brillouin spectroscopy describes the mechanical properties by means of the interaction of light with acoustic waves, spontaneously propagating in the matter due to thermal motions [12][13][14]. On the other hand, Raman spectroscopy is a well-established vibrational technique for the chemical characterization of organic material [15].…”
Section: Introductionmentioning
confidence: 99%